Soft tissue sarcoma stiffness and perfusion evaluation by MRE and DCE-MRI for radiation therapy response assessment: a technical feasibility study. (22nd May 2019) - Pepin, Kay; Grimm, Roger; Kargar, Soudabeh; Howe, B Matthew; Fritchie, Karen; Frick, Matthew; Wenger, Doris; Okuno, Scott; Ehman, Richard; McGee, Kiaran; James, Sarah; Laack, Nadia; et al.
Abstract: Soft tissue sarcomas are a rare and heterogeneous group of malignancies that present significant diagnostic and therapeutic challenges. Patient stratification based on tumor aggressiveness and early therapeutic response based on quantitative imaging may improve prediction of treatment response and the evaluation of new treatment strategies in clinical trials. The purpose of this pilot study was to determine the technical feasibility of magnetic resonance elastography (MRE) and dynamic contrast-enhanced (DCE) MRI for the evaluation of sarcoma stiffness and perfusion in 9 patients with histologically confirmed sarcoma. Additionally, we assessed the feasibility of utilizing MRE and DCE-MRI for the early evaluation of response to radiation therapy in 4 patients to determine the utility of further evaluation in a larger cohort study. Tumor size, stiffness, and perfusion parameters all decreased from baseline at the time of the pre-surgery or follow-up MRI, and results were compared to pathology or conventional imaging. MRE and DCE-MRI may be useful for the quantitative evaluation of tumor stiffness and perfusion, and therapy response assessment in soft tissue sarcomas.